The 'war on terror', state crime & radicalization: a constitutive theory of radicalization - Ahmed, Shamila (Palgrave studies in risk, crime and society, 2020)
This book examines the ‘war on terror’ and radicalization from an ontological, non-state centric perspective. Since 9/11, criminology has developed in its study of terrorism, utilising alternative non-state centric frameworks to uncover and make visible state-initiated harm. Although progress has been achieved, criminology has continued to privilege the state, thereby failing to uncover forms of state crime and how such crimes facilitate radicalization and terrorism. Ahmed aims to rectify this gap by demonstrating how crimes of the state have contributed to the existence of Islamist-inspired terrorism and the emergence of global Jihadist organisations like Al-Qaeda and ISIS. The ‘War on Terror’ abandons the dominant socially-constructed discourse and application of the ‘war on terror’ and instead favours a grounded approach whereby actors, actions and consequences are analysed according to the risk they represent. Ahmed achieves this grounded approach through situating state practices in international human rights law and international humanitarian law. Through documenting the intersectionality of these practices with radicalization in the emergence of global Jihadist organisations, the book demonstrates how state crimes contribute to terrorism. Although the book sits at the intersections of critical criminology, state crime, international/transnational crime, it is relevant to all disciplines that are concerned with state crime, terrorism and radicalization.